Clitoromegaly as first presentation of a neurocutaneous syndrome in a 3‐year‐old girl. Issue 9 (29th July 2015) - Karabouta, Zacharoula; Rousso, Israel; Athanassiadou‐Piperopoulou, Fani
Key Clinical Message: A rare cause of clitoral hypertrophy in a child is neurofibromatosis type 1 (NF1). Although evaluation, including karyotype and hormonal studies, is necessary to exclude ambiguous genitalia, the diagnosis of neurofibromatosis as a possible cause of clitoromegaly may help avoid lengthy and sometimes invasive interventions. Abstract : A rare cause of clitoral hypertrophy in a child is neurofibromatosis type 1. Although evaluation, including karyotype and hormonal studies, is necessary to exclude ambiguous genitalia, the diagnosis of neurofibromatosis as a possible cause of clitoromegaly may help avoid lengthy and sometimes invasive interventions.